Morphine selectively disinhibits glutamatergic input from mPFC onto dopamine neurons of VTA, inducing reward. (1st October 2020) - Yang, Li; Chen, Ming; Ma, Qianqian; Sheng, Huan; Cui, Dongyang; Shao, Da; Lai, Bin; Zheng, Ping
Abstract: Ventral tegmental area (VTA) dopamine (DA) neurons presynaptic glutamate release plays a very important role in the mechanism of morphine. Previously, a study from our lab found that morphine disinhibited glutamatergic input onto the VTA-DA neurons, which was an important mechanism for the morphine-induced increase in the VTA-DA neuron firing and related behaviors (Chen et al., 2015). However, what source of glutamatergic inputs is disinhibited by morphine remains to be elucidated. Using optogenetic strategy combined with whole-cell patch-clamp, qRT-PCR, immunofluorescence and chemical genetic approach combined with behavioral methods, our results show that: 1) morphine promotes glutamate release from glutamatergic terminals of medial prefrontal cortex (mPFC) neurons projecting to VTA-DA neurons but does not on those from glutamatergic terminals of the lateral hypothalamus (LH) neurons projecting to VTA-DA neurons; 2) different response of glutamatergic neurons projecting to VTA-DA neurons from the mPFC or the LH to morphine is related to the expression of GABAB receptors at terminals of these neurons; 3) inhibition of projection neurons from the mPFC to the VTA significantly reduces morphine-induced locomotor activity increase and conditioned place preference but inhibition of projection neurons from the LH to the VTA does not. These results suggest that morphine selectively promotes glutamate release of the glutamatergic input from mPFC onto VTA-DA neurons by removing the inhibition of the GABAB receptors in this glutamatergic input from mPFC. Highlights: Morphine promotes glutamate release from mPFC to VTA-DA neuron. Morphine has no effect on glutamate release from LH to VTA-DA neuron. Level of GABAB receptor in neuron from mPFC to VTA is higher than that from LH. Morphine promotes glutamate release from mPFC to VTA by removing GABAB -R effect. Inhibiting mPFC neurons projecting to VTA reduces morphine-induced behaviors.